Early and Non-invasive Diagnosis of Aspergillosis Revealed by Infection Kinetics Monitored in a Rat Model - Skriba, Anton; Pluhacek, Tomas; Palyzova, Andrea; Novy, Zbynek; Lemr, Karel; Hajduch, Marian; Petrik, Milos; Havlicek, Vladimir (Frontiers in Microbiology, 2018)
Aspergillus fumigatus is a ubiquitous saprophytic airborne fungus responsible for more than one million deaths every year. The siderophores of A. fumigatus represent important virulence factors that contribute to the microbiome-metabolome dialog in a host. From a diagnostic point of view, the monitoring of Aspergillus secondary metabolites in urine of a host is promising due to the non-invasiveness, rapidity, sensitivity and potential for standardization. Using a model of experimental aspergillosis in immunocompromised Lewis rats, the fungal siderophores ferricrocin (FC) and triacetylfusarinine C (TAFC) were monitored in rat urine before and after lung inoculation with Aspergillus fumigatus conidia. Molecular biomarkers were separated in high-dose (HD) and low-dose (LD) infection models using high performance liquid chromatography (HPLC) and were detected by mass spectrometry (MS). In the current work, we corroborated the in vivo MS infection kinetics data with micro-positron emission tomography/computed tomography (µPET/CT) kinetics utilizing 68Ga-labeled TAFC. In the HD model, the initial FC signal reflecting aspergillosis appeared as early as four hours post-infection. The results from seven biological replicates showed exponentially increasing metabolite profiles over time. In A. fumigatus, TAFC was found to be a less produced biomarker that exhibited a kinetic profile identical to that of FC. The amount of siderophores contributed by the inoculating conidia was negligible and undetectable in the HD and LD models, respectively. In the µPET/CT scans, the first detectable signal in HD model was recorded 48 hours post-infection. Regarding the MS assay, among nine biological replicates in the LD model, three animals did not develop any infection, while one animal experienced an exponential increase of metabolites and died on day six post-infection. All remaining animals had constant or random FC levels and exhibited few or no symptoms to the experiment termination. In the LD model, the TAFC concentration was not statistically significant, while the µPET/CT scan was positive as early as 6 days post-infection. Siderophore detection in rat urine by MS represents an early and non-invasive tool for diagnosing aspergillosis cased by A. fumigatus. µPET/CT imaging further determines the infection location in vivo and allows the visualization of the infection progression over time.